New challenge of the public buildings: nZEB findings from IEE RePublic_ZEB Project - Aelenei, Laura Elena (2016)
Nearly Zero-Energy Buildings (nZEBs) have received increased attention in recent years as a result of constant concerns for energy supply constraints, decreasing energy resources, increasing energy costs and rising impact of greenhouse gases on world climate. The EPBD recast directive [1] requests all new buildings to meet higher levels of performance than before, by exploring more the alternative energy supply systems available locally on a cost-efficiency basis and without prejudicing the occupants’ comfort. To this end, after 2020, all new buildings should become “nearly zero-energy” and after 31 December 2018, the same requirement is applied for new buildings occupied and owned by public authorities. Furthermore, the EPBD recast states that MS must ensure that minimum energy performance requirements for buildings are set with a view to achieving cost-optimal levels according to the Commission Delegated Regulation (EU) No 244/2012 of 16 January 2012. In this context, the authors of this paper, who are participants in the recent started European project RePublic_ZEB, are willing to share the initial findings from on- going research work. Public buildings constitute a specific class of buildings that require a complex analysis from the statistic point of view taking into consideration the definition and typologies and other specific parameters related with. Thus, this paper will focus on the analysis of public building stocks in the countries covered by the project consortium with the view to define relevant parameters characterizing the reference public buildings that will be considered in the further analysis regarding the assessment of cost-effective packages of solutions towards nZEB levels of performance. A review of nZEB holistic approach, definitions and existing implemented policies in the participant countries, will be presented as well.